Estados-Membros da Comunidade Económica dos Estados da África Ocidental Avaliação do grau de preparação para o comércio eletrónico - United Nations Conference on Trade; Development (United Nations, 2023)
The present assessment is part of the development of the Economic Community of West African States (ECOWAS) e-commerce strategy, for which UNCTAD was referred by the ECOWAS Commission in 2020. It documents the strengths, weaknesses and challenges that ECOWAS member States face in creating an enabling environment for the emergence of e-commerce and the digital economy, and is the first step in the preparation of the regional strategy. This diagnosis is predominantly based on updates of assessments already published, as well as seven rapid reviews conducted with countries that have not yet benefited from assessments.